Significados da experiência de re-inserção escolar: o Programa Projovem Urbano na perspectiva de seus protagonistas - Mascarenhas, Luciana Brandão Oliveira (2015)
This study investigated how young adults who experienced an irregular school trajectory, markedly of exclusion, make sense to the experience of school reinsertion in Projovem Urban Program in the city of Feira de Santana, Bahia. The study was conducted in one of the program's core located in Campo Limpo neighborhood. It sought to understand the uneven school trajectories and their meanings on the experience of schooling and it analyzed how processes of meaning engendered in the context of program can represent changes in the future projection. The study focuses on the perspective of the young as persons in development, which produces meanings in the construction of social relationships. It sought theoretical and methodological support in anepistemology of complexity approach, in an interdisciplinary way, located in the dialogue between the psychological perspective of Rede de Significações (RedeSig) and the Sociology of school experience. We use different strategies for the production of data: direct observation of context, with records in field diaries, informal conversations, focus group and narrative interviews, seeking to gather together different stories that intersect, making meaning networks. The results show that the forms of subjectivity that are built up over an irregular schooling produces an impact on the developmental trajectory of students when limit the possibilities for social inclusion. The “labyrinthic educational path is immersed in a network of meanings and sense that happen in multiple interactive fields in which they carry out the mediation of the school experience. Some networks may present more fragile than others and the school can promote or hinder the articulation of a "self-design”. Thus, the phenomenon of irregular trajectories experienced by many young Brazilians is associated with a broader social problem, because the ways of subjectivity articulate social positions, circumscribing different places in the social dynamics.